Profiles of teachers' concerns about heterogeneity in classrooms. Issue 7 (16th November 2020) - Dörrenbächer-Ulrich, Laura; Stark, Lisa; Perels, Franziska
ABSTRACT: Although recent research has focused on teachers' attitudes concerning inclusive education, studies on teachers' concerns about heterogeneity in inclusive education and on the implementation of inclusive teaching into their educational practice are sparse. Based on the concerns-based adoption model, the present study investigated whether there are different teacher profiles with regard to their concerns and behaviour regarding heterogeneity in inclusive classrooms and to what extent these profiles differ with regard to subjective dimensions (attitudes, subjective norms, self-efficacy, background factors such as experience and emotions). Three profiles merging teachers' Stages of Concern and Levels of Use (impact-concerned co-operators, unconcerned mechanical users, moderately concerned non-users) were identified in a sample of N  = 113 teachers. Moreover, substantial differences between the three profiles regarding all of the subjective dimensions were detected. It is discussed how these results can be used for supporting teachers in dealing with heterogeneity in inclusive education.